SYSTEMATICS AND SHELL MICROSTRUCTURE OF THE SPIRIFERID GENERA ECHINOSPIRIFER AND KOMISPIRIFER FROM THE UPPER DEVONIAN OF SOUTHERN TIMAN - Oleneva N.V. (My University, 2006)
The type species of the genera Echinospirifer Ljaschenko, 1973 Komispirifer Ljaschenko, 1973 and Mennespirifer Ljaschenko, 1973 were revised based on material from the memorial collection of A.I. Ljaschenko. Mennespirifer is recognized as a junior synonym of the genus Komispirifer; the genera Echinospirifer and Komispirifer differ in fine ornament and the structure of the shell wall. © Pleiades Publishing, Inc. 2006.
Keywords: FRASNIAN; SOUTHERNTIMAN; SPIRIFERIDS; UPPER DEVONIAN; Paleozoic::Devonian::Upper::Frasnian; Палеозой::Девонская::Верхний::Франский